YouTube : Audience emotional reactions and convergent alignment - Pelttari, Sanna (John Benjamins Publishing Company, 2022)
This case study discusses audiences’ emotional reactions and convergent alignment in YouTube comment threads observed on four videos of Spanish YouTubers with affective narratives on sensitive topics. The analysis reveals that most single-comment threads are generally positive and that utterances are fairly equally divided in their focus on YouTubers or narratives. The act of taking a stance follow consists of a versatile process in which the convergent alignment or agreement with the YouTubers’ stance lead occurs not just by positively evaluating YouTubers or the story, but also by revealing something highly private concerning the stance topic. The four affective narratives evoke not only compliments, but also the convergent alignment the YouTubers presumably seek with their stories.